Aging and FADS1 polymorphisms decrease the biosynthetic capacity of long-chain PUFAs: A human trial using [U-13C]linoleic acid. (September 2019) - Sasaki, Hideyuki; Sueyasu, Toshiaki; Tokuda, Hisanori; Ito, Mika; Kaneda, Yoshihisa; Rogi, Tomohiro; Kawashima, Hiroshi; Horiguchi, Sayaka; Kawabata, Terue; Shibata, Hiroshi
Highlights: We directly quantified the biosynthesis capacity of long-chain polyunsaturated fatty acids (LCPUFAs) using stable isotopic tracer in human. LCPUFA biosynthesis capacity largely differs by FADS1 rs174547 (T/C) polymorphism. LCPUFA biosynthesis capacity decreases with age in C allele carriers of rs174547 polymorphism. Abstract: Long-chain polyunsaturated fatty acids (LCPUFAs) are important constituents of biomembranes. Observation of blood fatty acids indicated that LCPUFA biosynthesis is affected by aging and FADS polymorphisms. This study examined the effects of aging and FADS polymorphisms on LCPUFA biosynthetic capacity via direct quantification using [U- 13 C]linoleic acid. Healthy young (25–34 years) and elderly (65–74 years) participants were administered [U- 13 C]linoleate, and its metabolites were monitored for 14 days. The time of maximum plasma concentration of 13 C-arachidonic acid (ARA) was 4–5 days. The area under the curve of the 13 C-ARA concentration differed by FADS1 rs174547 polymorphism (TT [100%] > TC [57%] > CC [37%]). Among C allele carriers, 13 C-ARA formation was 32% lower in elderly than in young participants. This is the first report to directly demonstrate that LCPUFA biosynthetic capacity is regulated by FADS1 polymorphisms and decreased by aging in FADS1 C allele carriers.